David Gordon White, The Yoga Sutra of Patanjali. A Biography (Altre Modernità, 2015)
David Gordon White, The Yoga Sutra of Patanjali. A Biography(Princeton, Princeton University Press, 2014, 273 pp. ISBN 978-0-691-14377-4) di Maria AngelilloDavid Gordon White,The Yoga Sutra of Patanjali. A Biography(Princeton, Princeton University Press, 2014, 273 pp. ISBN 978-0-691-14377-4)di Maria Angelillo